2012
DOI: 10.1021/jp303898g
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Solution Stability of Lysozyme in the Presence of Sucrose, Glucose, and Trehalose

Abstract: The effect of the sugars sucrose, glucose, and trehalose on the structural and colloidal stability of lysozyme has been investigated using differential scanning calorimetry and quasi-elastic light scattering, respectively. While sugars are known to increase the temperature at which thermal denaturation of protein occurs, it is not clear if, under the same solution conditions, greater colloidal stability is achieved. The measurements were carried out on lysozyme in three different buffer solutions, 0.05 M sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 49 publications
2
52
0
Order By: Relevance
“…In previous work, we have shown that while saccharides consistently increase T m , an increase in colloidal stability is only observed when the interaction potential is not dominated by electrostatic repulsion [20]. The presence of 20% v/v trehalose or maltose resulted in an increase in T m values; however, this increased thermal stability was not always accompanied by an increase in the proportion of refolded lysozyme.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In previous work, we have shown that while saccharides consistently increase T m , an increase in colloidal stability is only observed when the interaction potential is not dominated by electrostatic repulsion [20]. The presence of 20% v/v trehalose or maltose resulted in an increase in T m values; however, this increased thermal stability was not always accompanied by an increase in the proportion of refolded lysozyme.…”
Section: Discussionmentioning
confidence: 76%
“…The buffer type and pH range (pH 5 to pH 9) were chosen for a number of reasons. In previous work we have shown that for lysozyme, T m is pH dependent [20]. In that study, different buffer salts were used to obtain the desired pH (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that structural and colloidal stabilization depends on many other factors, such as pH, salt concentration, beside obviously the type of sugar [194].…”
Section: Protein Stability and Denaturationmentioning
confidence: 99%
“…8,25,33,34 These studies have shown that the effective inter-protein interaction potential results from the complex interplay of both attractive and repulsive contributions. 35 Proteins are inherently anisotropic, since each surface exposed amino acid contributes to varying degrees to the overall net-interaction potential. 9 This anisotropy has been shown to have a direct influence on protein phase behaviour.…”
Section: Introductionmentioning
confidence: 99%